Cambodian Dollarization: Its Policy Implications for LDCs’ Financial Development (Taylor & Francis, 2023)
This book is the first study to provide a comprehensive picture of the reality and structure of dollarization in Cambodia, which has been achieving rapid economic and financial development since the end of 1998, when full peace reigned over the kingdom. It uses the micro-level data collected through nationwide surveys conducted jointly by the National Bank of Cambodia and JICA Ogata Sadako Research Institute in 2014 and 2017. By applying econometric analysis to collected data, the book analyses in detail the structures and mechanisms of dollarization in households, companies, and financial institutions. It also provides detailed information on the historical development of Cambodian dollarization, international comparisons with various cases of dollarization in countries around the world, and the impact of NBC's digital payment platforms (particularly Bakong) on the use of local and foeign currencies. The Cambodian case shows that financial development of low- and middle-income countries is promoted mutually by dollarization and that policies to separate the two are necessary to curb dollarization. This book will be of interest to students, researchers and policy-makers concerned with dollarization and economics in Southeast Asia.